Pengembangan Lembar Kerja Peserta Didik Berbantuan Socrative pada Pembelajaran Teks Cerpen untuk Meningkatkan Hasil Belajar Siswa Kelas XI Sekolah Menengah Atas Negeri 16 Medan - Dwi Putri Maulidiyah; Nila Safina; Rika Kartika (Medan Resource Center, 2025)
The integration of digital learning media in language instruction has become increasingly important to enhance students’ engagement and learning outcomes. This study aims to develop, examine the feasibility, and evaluate the effectiveness of Socrative-assisted student worksheets for short story text learning among eleventh-grade students at State Senior High School Sixteen Medan. Employing a Research and Development approach, the study adopts the Borg and Gall development model. The research population consisted of 384 students, with a sample of 35 eleventh-grade students selected for limited field testing. Data were collected through expert validation, teacher assessments, student responses, and learning outcome evaluation tests. The feasibility analysis indicates that the developed worksheets are categorized as highly feasible, as evidenced by assessments from media experts (91% and 88%), material experts (86% and 94%), an Indonesian language teacher (96%), and student trials (92%). Furthermore, the effectiveness test demonstrates that the Socrative-assisted worksheets significantly improve students’ learning outcomes, achieving an effectiveness score of 93%, which falls within the highly effective category. It can be concluded that Socrative-assisted student worksheets for short story texts are pedagogically sound, practically applicable, and effective in enhancing students’ learning outcomes in Indonesian language learning.